The Cognitive-Enhancing Effects of Dendrobium nobile Lindl Extract in Sleep Deprivation-Induced Amnesic Mice - Jiang, Ning; Li, Yu-jiao; Wang, Meng-di; Huang, Hong; Chen, Shanguang; Li, Yinghui; Qu, Lina; Wang, Fengzhong; Liu, Xinmin; Wang, Qiong (Frontiers in Psychiatry, 2022)
Chronic sleep deprivation (SD) causes neurological and neurodegenerative dysfunction including learning and memory deficit. The orchid Dendrobium nobile Lindl (DN), is widely used as a Yin tonic and medicinal food throughout Asia, and has many reported pharmacological effects. This study focused on the cognitive-enhancing effects of DN in sleep deprivation-induced amnesic in mice and its biochemical mechanisms. Our results showed that the mice displayed significant cognitive deficits after 14-days’ SD, while treatment with the extract of DN prevented these impairments. In novel object recognition task and object location recognition task, a significant increase in discrimination index were observed in DN-treated (200 and 400mg/kg) mice. In MWM test, DN ((200 and 400mg/kg)) treatment shorten the prolongation of latency and increased the crossing numbers compared with SD mice. The biochemical analysis of brain tissue showed a decrease in NE, dismutase (T-SOD) and catalase (CAT) activity and a increase in 5-HT and malondialdehyde (MDA) concentration after the treatment with DN in mice. Our findings indicated that DN exerted positive effect in preventing and improving cognition impairment induced by SD, and suggested it might be related to mediated the regulation of neurotransmitters and alleviation of oxidative stress. Abbreviations: CSI, chronical sleep interruption; DI, discrimination index; DN, Dendrobium nobile Lindl; LC-MS/MS, liquid chromatography-tandem mass spectrometry; MWM, Morris water maze; NOR, novel object recognition; OLR, object location recognition.